Major Health Problems and Diseases of Street Dogs in Pokhara Valley, Nepal - Acharya, Mohan; Dhakal, Santosh (International Journal of Applied Sciences and Biotechnology, 2016)
Objective of the study was to find the prevalence of major health problems among street dogs in Pokhara Valley, Nepal. Data were taken from the rescued street dogs brought for the treatment at Himalayan Animal Rescue Team (HART), Nepal, from January to December, 2011. A total of 171 sick or injured dogs were brought for the treatment. All the preliminary diagnosis was done by the veterinary officer and confirmatory diagnosis were limited. Data were analyzed using Microsoft excel program 2013 (Microsoft Corporation, New York, USA) and results are presented as number and in percentage. Mange infestation (40.35%) was the most prevalent problem, followed by general wound (18.12%), respiratory tract infection (7.60%), gastrointestinal parasites (5.26%), and general nervous signs (4.09%). Two dogs were suspected with rabies. Maggot infestations, tick infections, poisoning, bone fractures, otitis, pyometras, bite wounds, mammary tumors, hernias, abscesses, and anemic conditions collectively accounted for nearly 24.58%. Results presented in this study can be a reference for non-government organizations involving in rescue and treatment of sick and injured street dogs to plan their activities. Int J Appl Sci Biotechnol, Vol 4(1): 53-56